National Parks - Management and Conservation 2018
DOI: 10.5772/intechopen.72782
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Interpretation in the Management of National Parks in South Africa

Abstract: National parks and protected areas are under dichotomy of pressures. On the one hand, they are faced with increasing economic burdens to become independent from state and donor grants, and on the other hand, they need to fulfill their mandate of conserving the environment for future generations. The South African National Parks (SANParks) is no different. Operating costs for managing 19 national parks are roughly 1 billion rand and requires management to generate 80% thereof in order to meet their primary mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The second aspect, activity involvement, refers to cuisine experiences, events and local culture and therefore indicates that visitors to KTP require interpretation services that focus on the heritage and culture within the park. This was confirmed by Mearns and Botha (2017), who explain that heritage and culture form part of natural area interpretation.…”
Section: Interpretation Services Needed By Visitorsmentioning
confidence: 67%
See 2 more Smart Citations
“…The second aspect, activity involvement, refers to cuisine experiences, events and local culture and therefore indicates that visitors to KTP require interpretation services that focus on the heritage and culture within the park. This was confirmed by Mearns and Botha (2017), who explain that heritage and culture form part of natural area interpretation.…”
Section: Interpretation Services Needed By Visitorsmentioning
confidence: 67%
“…Customising interpretation services to the tourists' needs and preferences may add to the visitors' enjoyment, create loyalty, extend stays, and increase expenditure and revenue for parks (Mearns & Botha 2017). Interpretation is therefore no longer seen as a 'luxury' service but is rather viewed worldwide as an essential management function of national parks, and this is also the case in KTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven (12%) studies examined heritage interpretation contextually, while four studies (7%) identified new concepts in heritage interpretation and 7% linked heritage interpretation as a tool for sustainable development. Role of interpretation in protected areas Moscardo et al, 2004;Trobec, 2015;Mearns & Botha, 2018;Klitsounova, 2020 7% Interpretation planning, management, and evaluation Orams, 1996;Archer & Wearing, 2001;Wearing & Archer, 2003;Ham & Sandberg, 2012;Robert et al, 2014;Quetel-Brunner & Griffin, 2014;Krisma & Marhaento, 2021;Juma & Khademi-Vidra, 2022;Maringer & Blank, 202316% Environmental interpretation Obua, 2003Munro et al, 2008;Xu et al, 2013;Shittu, 2013;Ren & Folta, 2016;Phan & Schott, 2017;Dussler & Deringer, 2020;Tang et al, 2022;Zhang et Next, the content of each grouped deemed most pertinent to the current or potential role of heritage interpretation in stimulating ecotourism in protected areas was identified, analysed, and synthesized based on a narrative or thematic approach proposed by Arksey and O'Malley (2005), to present a narrative justification of the existing research:…”
Section: Thematic Areas In the Literaturementioning
confidence: 99%
“…Many authors point to the role of interpretation in PAs and how through interpretation, visitors gain knowledge, people's attitudes and behaviours are changed, and tourists are encouraged to take care of the PAs and become more responsible citizens (Klitsounova, 2020;Mearns & Botha, 2018;Trobec, 2015). Furthermore, heritage interpretation can be used to solve key challenges facing PAs, such as effective management of national parks, increasing popularity, implementing sustainable tourism, and raising public awareness of the importance of parks' natural and cultural heritage (Trobec, 2015).…”
Section: Role Of Heritage Interpretation In Protected Areasmentioning
confidence: 99%